Ocular development after highly effective modulator treatment early in life - Yimin Zhu; Danni Li; Felisa Reyes-Ortega; Felisa Reyes-Ortega; Holly R. Chinnery; Elena K. Schneider-Futschik (Frontiers Media S.A., 2023)
Highly effective cystic fibrosis (CF) transmembrane conductance regulator (CFTR) modulator therapies (HEMT), including elexacaftor-tezacaftor-ivacaftor, correct the underlying molecular defect causing CF. HEMT decreases general symptom burden by improving clinical metrics and quality of life for most people with CF (PwCF) with eligible CFTR variants. This has resulted in more pregnancies in women living with CF. All HEMT are known to be able pass through the placenta and into breast milk in mothers who continue on this therapy while pregnant and breast feeding. Toxicity studies of HEMT in young rats demonstrated infant cataracts, and case reports have reported the presence of congenital cataracts in early life exposure to HEMT. This article reviews the evidence for how HEMT influences the dynamic and interdependent processes of healthy and abnormal lens development in the context of HEMT exposure during pregnancy and breastfeeding, and raises questions that remain unanswered.